Решить уравнение: 0,5(2y-1)-(0,5-0,2y)+1=0; (x в кв.+3x+2)(x в кв.+3x+4)=8; (x в кв.-2x-3)(4-x в кв.+2x)=-2; (x в кв.-x-11)(x в кв.-x-21)=-9; (x-1/x) в кв.+3(1/x-x)=4 2p-1/6| - |p+1/3=p; 12-x/4| - |2-x/3=x/6; Найти корень уравн...

Решить уравнение: 0,5(2y-1)-(0,5-0,2y)+1=0; (x в кв.+3x+2)(x в кв.+3x+4)=8; (x в кв.-2x-3)(4-x в кв.+2x)=-2; (x в кв.-x-11)(x в кв.-x-21)=-9; (x-1/x) в кв.+3(1/x-x)=4 2p-1/6| - |p+1/3=p; 12-x/4| - |2-x/3=x/6; Найти корень уравнения: 1-(x-3/2)=(2-x/3)+4
Гость
Ответ(ы) на вопрос:
Гость
1) 0,5(2y-1) - (0.5-0.2y)+1=0 1y-0.5-0.5+0.2y+1=0 1.2y=0 y=0 Ответ: 0 2) (x² +3x+2)(x² +3x+4)=8 (x² +3x+2)(x² +3x+2+2)=8 y=x² +3x+2 y(y+2)=8 y² +2y-8=0 D=4+32=36 y₁=(-2-6)/2= -4 y₂=(-2+6)/2=2 При у= -4 x² +3x+2= -4 x² +3x+2+4=0 x² +3x+6=0 D=9-24<0 нет решений. При у=2 x² +3x+2=2 x² +3x+2-2=0 x² +3x=0 x(x+3)=0 x=0       x+3=0              x= -3 Ответ: -3;  0. 3) (x² -2x-3)(4-x² +2x)= -2 (x² -2x-3)*(-(x² -2x-4))= -2 (x² -2x-3)(x² -2x-3-1)=2 y=x² -2x-3 y(y-1)=2 y² -y-2=0 D=1+8=9 y₁=(1-3)/2= -1 y₂=(1+3)/2=2 При у= -1 x² -2x-3= -1 x² -2x-3+1=0 x² -2x-2=0 D=4+8=12 x₁=(2-√12)/2=(2-2√3)/2=1-√3 x₂=1+√3 Ответ: 1-√3;  1+√3 4) (x² -x-11)(x² -x-21)= -9 (x² -x-11)(x² -x-11-10)= -9 y=x² -x-11 y(y-10)= -9 y² -10y+9=0 D=100-36=64 y₁=(10-8)/2=1 y₂=(10+8)/2=9 При у=1 x² -x-11=1 x² -x-11-1=0 x² -x-12=0 D=1+48=49 x₁=(1-7)/2= -3 x₂=(1+7)/2=4 При у=9 x² -x-11=9 x² -x-11-9=0 x² -x-20=0 D=1+80=81 x₁=(1-9)/2= -4 x₂=(1+9)/2=5 Ответ: -4; -3; 4; 5.
Не нашли ответ?
Ответить на вопрос
Похожие вопросы